2016
DOI: 10.1007/s00223-016-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine Upregulates Osteogenesis by Human Mesenchymal Stem Cells In Vitro and Accelerates Bone Development in Rats

Abstract: Theobromine (THB) is one of the major xanthine-like alkaloids found in cacao plant and a variety of other foodstuffs such as tea leaves, guarana, and cola nuts. Historically, THB and its derivatives have been utilized to treat cardiac and circulatory disorders, drug-induced nephrotoxicity, proteinuria and as an immune-modulator. Our previous work demonstrated that THB has the capacity to improve the formation of hydroxyl-apatite during tooth development, suggesting that it may also enhance skeletal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The supplementation with theobromine (the compound present in Theobroma cacao) has beneficial effects on the bone health of rats (longer and thicker femurs and better tibial trabecular parameters). 31,32 However, our study showed no significant difference in the bone mineral content and the bone area of animals supplemented with cocoa powder, suggesting the need for further studies to clarify the effects of cocoa administration on bone parameters.…”
Section: Discussionmentioning
confidence: 53%
“…The supplementation with theobromine (the compound present in Theobroma cacao) has beneficial effects on the bone health of rats (longer and thicker femurs and better tibial trabecular parameters). 31,32 However, our study showed no significant difference in the bone mineral content and the bone area of animals supplemented with cocoa powder, suggesting the need for further studies to clarify the effects of cocoa administration on bone parameters.…”
Section: Discussionmentioning
confidence: 53%
“…2). A previous report showed that theobromine, a natural xanthine derivative, stimulated bone formation at a high concentration [19]. Although both xanthine derivatives have similar effects on osteoblasts, KPR-A148 is structurally distinct from theobromine, indicating that KPR-A148 is a new xanthine derivative capable of inducing osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 94%
“…Theobromine exposure on human mesenchymal stem cells promoted osteogenesis and the rate of mineralization. Also, oral administration of theobromine via dietary food from pregnancy until postnatal days accelerated the bone development in rats [19]. Pentoxifylline [3,7-dimethyl-1-(5-oxohexyl) purine-2,6-dione], a synthetic xanthine derivative, has also been reported to have a positive effect on bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro results showed that theobromine upregulated osteogenesis and simultaneously downregulated adipogenesis by MSCs (36). Therefore, changes in other functions of stem cells by theobromine, such as their interaction with immune cells, are plausible.…”
Section: Discussionmentioning
confidence: 95%